Influence of different bedding material on locomotor behaviour of thoroughbred horses housed in individual stalls (Indian Journal of Animal Production and Management, 2024)
The effect of three different bedding material on the locomotor behaviour of horses housed in individual boxes were analysed. Three different groups of horses, with ten horses in each group, were kept on straw bedding, wood shavings and no bedding material for four weeks. A behaviour recording chart was used to not each individual’s behaviour for four hours a day (morning and evening). Recording time for the behaviour like standing on three legs, body stretching, kicking behaviour, walking in the stable, scratching of body with legs and lying behaviour with bedding were generated. Use of straw bedding caused a significantly higher frequency and total duration of standing on three legs (P
Keywords: Horses; Bedding material; Locomotor behaviour; Individual stall